2019
DOI: 10.1515/bot-2018-0069
|View full text |Cite
|
Sign up to set email alerts
|

The seaweed resources of the Philippines

Abstract: This review paper presents information on the production status of economically important seaweed species in the Philippines, new culture technologies for Halymenia durvillei and also an examination of the present but limited use of Sargassum. The country recorded its highest production volume of seaweeds (mainly eucheumatoids) in 2011 amounting to 1,840,832 metric tons (fresh weight). In the subsequent years, the Philippines recorded a steady decline in production which can be attributed to epiphytism, loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 67 publications
0
54
0
10
Order By: Relevance
“…Plurangial cuticles in Ch. minima have not been mentioned in other reports (Fotos 1981, Trono 1997, Abbott and Huisman 2004, Kraft 2009. Kraft (2009) suggested that the plurangia illustrated by Fotos (1981, figs.…”
Section: Discussionmentioning
confidence: 79%
“…Plurangial cuticles in Ch. minima have not been mentioned in other reports (Fotos 1981, Trono 1997, Abbott and Huisman 2004, Kraft 2009. Kraft (2009) suggested that the plurangia illustrated by Fotos (1981, figs.…”
Section: Discussionmentioning
confidence: 79%
“…Alga K. alvarezii adalah alga yang dibudidayakan secara komersial karena merupakan komoditi penting penghasil kappa karagenan. Ciri morfologi dari K. alvarezii adalah thallus yang silindris dengan permukaan yang licin dan kartilogenus (Trono, 1997). Warna thalus tidak tetap tergantung faktor lingkungan terkadang berwarna coklat, hijau, kuning dan kemerahan (Luning, 1990 (Sunarto, 2008).…”
Section: Pendahuluanunclassified
“…Makroalga dapat dijumpai hidup dan melekat pada tipe substrat seperti pasir, berlumpur, bahkan pada tipe substrat keras seperti karang dan batu. Makroalga hidup dengan menancapkan dirinya pada substrat berlumpur, pasir, karang, karang mati, kulit kerang, batu, kayu bahkan sebagai epifit dengan menancapkan dirinya pada tumbuhan lain (Trono, 1997). Odum (1996) (Bold dan Wynne, 1985).…”
Section: Habitat Makroalgaunclassified